PENERAPAN MODELPROBLEM BASED LEARNINGUNTUKMENINGKATKAN KEMAMPUAN PEMECAHANMASALAHMATEMATIS PESERTA DIDIKKELAS X MIA MA MUHAMMADIYAH PEKANBARU - Mardiyanti, Tiska; Roza, Yenita; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to improve the learning process and the student?s mathematical problem solving skill by applying Problem Based Learningmodel. This type of research is classroom action research with two cycles. This research was conducted in collaboration between researcher and teacher of mathematics. Subjects were students of class X MIA MA Muhammadiyah Pekanbaru. The study was conducted in the first semester of academic year 2019/2020. The research instrument consists of mathematical learning instruments and instruments to collect data. Mathematical learning instruments used in this study are syllabus, lesson plans, and activity sheets. Data collection instruments used in this study is observation sheets and mathematical problem solving tests. Data analysis technique in this study is analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. The result of this study showed that the implementation of PBL improved the learning process and the student?s mathematical problem solving skill. The student?s average scorein cycle I which is 70,92had improved to 86,98in cycle II. The improvement also foundin the indicator average scorein identifying the problem, devising a plan to solve the problem, carrying out the plan to solve the problem, and interpreting the solution. This study concludes that the implementation of PBL improved the learning process and the student?s mathematical problem solving skill at class X MIA MA Muhammadiyah Pekanbaru. PBL model can be used as an alternative to learning, because through this learning can improve the learning process and mathematical problem solving skill of the students.Key Words:Problem Based Learning, Mathematical Problem Solving Skill, Learning Process.